2014
DOI: 10.1016/j.cell.2014.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Successful Execution of Working Memory Linked to Synchronized High-Frequency Gamma Oscillations

Abstract: Neuronal oscillations have been hypothesized to play an important role in cognition and its ensuing behavior, but evidence that links a specific neuronal oscillation to a discrete cognitive event is largely lacking. We measured neuronal activity in the entorhinal-hippocampal circuit while mice performed a reward-based spatial working memory task. During the memory retention period, a transient burst of high gamma synchronization preceded an animal's correct choice in both prospective planning and retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
330
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 320 publications
(355 citation statements)
references
References 44 publications
25
330
0
Order By: Relevance
“…Second, the injection of a mixture of their respective antagonists for mGluR1 and cholinergic muscarinic receptors into the dMEC inhibits trace fear conditioning in control mice, but not in dMECIII-TeTX mutant mice (Suh et al 2011). Finally, as described earlier the dMECIII-TeTX mutant mice had deficits in a DNMP task (Suh et al 2011;Yamamoto et al 2014). Yamamoto et al (2014) found ramping phasic multiunit activity (MUA) bursts in dMECIII during test trials of the DNMP task in control animals.…”
Section: The Hippocampal Ca1 Area Supports Temporal Associative Learningmentioning
confidence: 53%
See 1 more Smart Citation
“…Second, the injection of a mixture of their respective antagonists for mGluR1 and cholinergic muscarinic receptors into the dMEC inhibits trace fear conditioning in control mice, but not in dMECIII-TeTX mutant mice (Suh et al 2011). Finally, as described earlier the dMECIII-TeTX mutant mice had deficits in a DNMP task (Suh et al 2011;Yamamoto et al 2014). Yamamoto et al (2014) found ramping phasic multiunit activity (MUA) bursts in dMECIII during test trials of the DNMP task in control animals.…”
Section: The Hippocampal Ca1 Area Supports Temporal Associative Learningmentioning
confidence: 53%
“…Finally, as described earlier the dMECIII-TeTX mutant mice had deficits in a DNMP task (Suh et al 2011;Yamamoto et al 2014). Yamamoto et al (2014) found ramping phasic multiunit activity (MUA) bursts in dMECIII during test trials of the DNMP task in control animals. The MUA bursts of dMECIII in the dMECIII-TeTX mutant mice during test trials were much weaker than those in control mice.…”
Section: The Hippocampal Ca1 Area Supports Temporal Associative Learningmentioning
confidence: 53%
“…Gamma band oscillations are linked with performance of working memory tasks (Yamamoto et al;Howard et al, 2003;Roux and Uhlhaas, 2014), where patients show impairment (Perlstein et al, 2001;Bor et al, 2011). Indeed, the deficits in gamma oscillatory activity in patients are correlated with working memory deficits (Cho et al, 2006).…”
Section: The Trn and Schizophrenia Risk Factors: Preclinical Evidencementioning
confidence: 99%
“…Spike-time synchronization may organize populations of neurons that are engaged in cognitive behaviors (18)(19)(20). The contribution of the recurrent cortical connections in the generation of synchronized neural populations has been previously emphasized (26).…”
Section: Discussionmentioning
confidence: 99%
“…Feedback connections may also participate in generating spike-time synchronization among populations of neurons that are engaged in cognitive behaviors (18)(19)(20) by the same mechanisms described here for propagation of synchronized spikes through cortical areas.…”
mentioning
confidence: 89%